已知数列{an}中,a1=1,an+1=
(1)求数列{an}的通项公式an; (2)设:
(3)已知P=(1+b1)(1+b3)(1+b5)…(1+b2n-1),求证:Pn>
|
(1)由an+1=
得:an 2an+1
-1 an+1
=2且1 an
=1,1 a1
所以知:数列{
}是以1为首项,以2为公差的等差数列,1 an
所以
=1+2(n-1)=2n-1,得an=1 an
.1 2n-1
(2)由
=2 bn
+1得:1 an
=2n-1+1=2n,∴bn=2 bn
,1 n
从而:bnbn+1=
,1 n(n+1)
则 Tn=b1b2+b2b3+…+bnbn+1=
+1 1×2
+…+1 2×3 1 n(n+1)
=(1-
)+(1 2
-1 2
)+(1 3
-1 3
)+…+(1 4
-1 n
)1 n+1
=1-
=1 n+1
.n n+1
(3)已知Pn=(1+b1)(1+b3)(1+b5)…(1+b2n-1)=
×2 1
×4 3
×…×6 5
,2n 2n-1
∵(4n)2<(4n)2-1,∴
<2n+1 2n 2n 2n-1
设:Tn=
×3 2
×…×5 4
,则Pn>Tn2n+1 2n
从而:Pn2>PnTn=
×2 1
×3 2
×…×4 3
×2n 2n-1
=2n+1,2n+1 2n
故:Pn>
.2n+1